Molecular Comparison of Adult and Pediatric Ulcerative Colitis Indicates Broad Similarity of Molecular Pathways in Disease Tissue. Issue 1 (July 2018) - Li, Katherine; Strauss, Richard; Ouahed, Jodie; Chan, Daphne; Telesco, Shannon E.; Shouval, Dror S.; Canavan, James B.; Brodmerkel, Carrie; Snapper, Scott B.; Friedman, Joshua R.
ABSTRACT: Background: Efficacy data from adult ulcerative colitis (UC) clinical trials are often extrapolated for pediatric prescribing. Consequently, it is important to understand similarities/differences in pediatric and adult UC. Pediatric UC tends to have more extensive disease at presentation, yet genetic studies have not detected pathways that distinguish the populations, and differences in mucosal gene expression between adult and pediatric UC are not well characterized. Methods: Using colonic microarray data from a phase 3 trial of golimumab in adult UC (87 UC; 21 healthy), the GSE10616 pediatric dataset (10 UC; 11 healthy), and a phase 1B trial of golimumab in pediatric UC (n = 19), UC expression profiles were compared and unique genes were defined as those with significant changes (|FC|>2×, adjusted P < 0.05) in one population, but not the other (|FC| < 1.2×, adjusted P > 0.05). Pathway and upstream regulator analyses were performed. Profiles by disease extent (extensive [pancolitis] vs limited [left-sided] involvement) were compared within each population. Results: Pediatric and adult disease profiles overlapped substantially, with ∼50% to 75% overlap, depending on the fold-change cutoff used. Conversely, <10% of the disease profiles were unique to each population. Similar canonical pathways were enriched in both datasets. Predicted upstream regulators were also concordant, including lipopolysaccharide, interleukin-1β, and tumor necrosis factor-α. Expression profiles of extensive UC were indistinguishable from those of patients with limited involvement in each population. Conclusions: The UC gene expression landscape is shared by adults and children, independent of disease extent. This supports extrapolation of efficacy from adults to children in developing new therapies for UC. Abstract : Supplemental Digital Content is available in the text